The Global Environment Facility in MENA - Kayser, Dominique Isabelle (World Bank, Washington, DC, 2014)
Environmental stress is a serious concern in the Middle East and North Africa (MENA) region. Recent years have witnessed important changes that are pushing the boundaries of the region's environmental legacy. The current trends are declining water resources per capita, shrinking arable land, deteriorating vulnerable coastal zones and marine resources, rising energy use, and mounting pollution, particularly in urban areas. This environmental degradation would imply considerable costs and significant harm to livelihoods, public finances, and the economic competitiveness of the region. Recognizing this, over the past two decades important efforts have been made, at both national and regional levels, to enhance environmental management and protection. The World Bank's partnership with the Global Environment Facility (GEF) focuses on long-term development founded on uses of natural capital that are optimized and sustainable. This MENA knowledge and learning quick note summarizes the two decades of World Bank GEF-funded work in support of the environment that has contributed to the MENA region's environmental, health, and social and economic development, and points to opportunities for further cooperation in support of green growth.